2016
DOI: 10.1007/s12035-015-9678-0
|View full text |Cite
|
Sign up to set email alerts
|

A Nonrewarding NMDA Receptor Antagonist Impairs the Acquisition, Consolidation, and Expression of Morphine Conditioned Place Preference in Mice

Abstract: N-methyl-D-aspartate (NMDA) receptor antagonists block morphine-induced conditioned place preference (CPP). Although polyamines are endogenous modulators of the NMDA receptor, it is not known whether polyaminergic agents induce CPP or modulate morphine-induced CPP. Here, we examined whether polyamine ligands modify morphine CPP acquisition, consolidation, and expression. Adult male albino Swiss mice received saline (0.9 % NaCl, intraperitoneally (i.p.)) or morphine (5 mg/kg, i.p.) and were respectively confine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 101 publications
0
5
0
Order By: Relevance
“…injection, while SCH and RAC were intraperitoneally injected 30 min before METH injection at doses of 0.03 mg/kg and 2.0 mg/kg, respectively [ 33 , 34 ]. For conditioned place preference (CPP) test, METH (1.0 mg/kg) [ 35 ], cocaine (10.0 mg/kg) [ 36 ] and morphine (10.0 mg/kg) [ 37 ] were each intraperitoneally injected, while SPD and Arc were intraperitoneally injected 30 min before METH at doses of 30.0 mg/kg and 3.0 mg/kg respectively [ 38 ]. SKF and QNP were each intraperitoneally injected daily at doses of 5.0 mg/kg and 0.5 mg/kg respectively for repeated 7 days [ 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…injection, while SCH and RAC were intraperitoneally injected 30 min before METH injection at doses of 0.03 mg/kg and 2.0 mg/kg, respectively [ 33 , 34 ]. For conditioned place preference (CPP) test, METH (1.0 mg/kg) [ 35 ], cocaine (10.0 mg/kg) [ 36 ] and morphine (10.0 mg/kg) [ 37 ] were each intraperitoneally injected, while SPD and Arc were intraperitoneally injected 30 min before METH at doses of 30.0 mg/kg and 3.0 mg/kg respectively [ 38 ]. SKF and QNP were each intraperitoneally injected daily at doses of 5.0 mg/kg and 0.5 mg/kg respectively for repeated 7 days [ 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…Excessive production of NO is involved in several pathological forms of neural plasticity, such as opioid tolerance, dependence, and reward 1,7,8 . NMDAR antagonists such as MK‐801 attenuate these negative effects of opioids 9–12 . However, their clinical use is limited by adverse side effects (e.g., learning and memory impairment, motor ataxia, cognitive dissociation, and increased lethality) 13–17 .…”
Section: Introductionmentioning
confidence: 99%
“…1,7,8 NMDAR antagonists such as MK-801 attenuate these negative effects of opioids. [9][10][11][12] However, their clinical use is limited by adverse side effects (e.g., learning and memory impairment, motor ataxia, cognitive dissociation, and increased lethality). [13][14][15][16][17] Neuronal nitric oxide synthase (nNOS) catalytic inhibitors also suppress opioid reward, tolerance, and dependence 1,5,[18][19][20] but lack of isoform selectivity similarly contributes to unwanted side effects.…”
mentioning
confidence: 99%
“…Considering the essential role of the NAc as a key structure in motivation and memory, Ahmadi and colleagues have demonstrated that systemic administration of morphine may induce passive avoidance memory through NMDA function in the NAc [33]. In another study, it was established that NMDA receptors in the NAc are involved in the reconsolidation of aversive and positive morphine-associated memories [34][35][36].…”
Section: Discussionmentioning
confidence: 99%